Health screening and autogenous vaccination strategies for atypical Aeromonas salmonicida in farmed ballan wrasse (Labrus bergylta, Ascanius) - Papadopoulou, Athina (University of Stirling, 2019)
Ballan wrasse (Labrus bergylta, A.) are deployed in Atlantic salmon (Salmo salar, L.) pens to control sea lice (Lepeophtheirus salmonis, K) infestations in the Northern hemisphere. Bacterial disease outbreaks related to atypical Aeromonas salmonicida (aAs), however, cause significant mortalities in ballan wrasse at hatcheries and cage sites. Although a multivalent autogenous vaccine, including aAs, was being used disease outbreaks still occurred. The aims of this project were initially to identify the most prevalent and predominant bacterial pathogens from ballan wrasse in hatcheries and cage sites in Scotland with the goal of optimising the formulation of the autogenous vaccine used in hatcheries (Chapter 3). Then, the effect of the enzyme Alcalase® was investigated on bacterial load which could provide essential information for disinfection protocols in commercial hatcheries (Chapter 4). Also, the egg microbiota of farmed ballan wrasse was characterised shortly after spawning and during incubation, and the possibility of vertical transmission of aAs from broodstock to offspring was investigated. The above would give an insight into egg bacteria dynamics and possibly identify when ballan wrasse encounter important bacterial pathogens during production (Chapter 4). Furthermore, the pathogenicity and virulence of bacterial isolates collected during disease outbreaks in Scotland were evaluated and experimental bacterial challenge models were developed both by bath and i.p injection. These had the objective to determine the efficacy of the immersion and injectable version of the autogenous polyvalent vaccine that has been used in commercial hatcheries (Chapter 5, 6 and 7). Finally, the ontogeny of elements of the adaptive immune system of farmed ballan wrasse was verified on juvenile ballan wrasse (Chapter 7). Atypical As was the most prevalent and predominant bacterial species isolated during the health survey (Chapter 3) with Vibrionaceae isolates also recovered from diseased fish. The former bacterium was ...